Risk Profile of Bacteriophages in the Food Chain - Monika Trząskowska; Eyesun Eedo Naammo; Muhammad Salman; Ayomide Afolabi; Catherine W. Y. Wong; Danuta Kołożyn-Krajewska (Foods)
Phages are considered effective biocontrol agents for improving food safety due to their specific interaction with pathogens. It is essential to recognise that zero risk does not exist, and as biological agents, phages must be continuously evaluated for potential adverse effects on human health in both food and clinical contexts. This is the first bacteriophage risk profile performed according to the methodology recommended by FAO/WHO and EFSA. Key safety concerns regarding phage use in the food sector include the risk of horizontal gene transfer, especially regarding antibiotic resistance genes among bacteria. While such occurrences are contextually dependent and rare, they warrant further scrutiny. Moreover, improper phage application during food processing could lead to the emergence of resistant bacterial strains, compromising the long-term efficacy of phage interventions. Currently, there is limited evidence indicating any health risks linked to phage consumption or pathogenic behaviour (e.g., possible association between bacteriophages and Parkinson’s disease). Despite numerous studies affirming the safety and efficacy of phages in the food chain, continuous monitoring remains crucial. In particular, the responses of susceptible populations to phage exposure should be carefully examined.